Protagonismo de Ana Carolina Costa Pereira no campo da educação matemática: Ana Carolina Costa Pereira's leading role in the field of mathematics education - Nogueira de Oliveira, Adriana; Andrade de Sousa, Francisca Genifer; Fialho, Lia Machado Fiuza (Revista Cocar, 2021)
A pesquisa objetivou biografar Ana Carolina Costa Pereira com ênfase no seu envolvimento no campo da educação matemática e na sua atuação docente (2013-2021). Ancora-se teoricamente nos pressupostos da História Cultural para desenvolver uma biografia hermenêutica mediante entrevista livre em história oral desenvolvida com a própria biografada. Os resultados inferem que Ana Carolina é uma mulher que contou com formação privilegiada em instituições de educação básica particulares de Fortaleza-CE, seguida da graduação em Matemática, mestrado, doutorado e pós-doutorado em universidades públicas no campo da educação matemática. A sua prática pedagógica é alicerçada pela relação horizontal com os discentes e no desenvolvimento de aulas interativas e contextualizadas que incentivam à criticidade. Demonstra-se a expertise de uma mulher no campo matemático, historicamente dominado por homens. Palavras-chave: Biografia; Educação de mulheres; Educação Matemática; Mulher na ciência. Abstract The research aimed to biography Ana Carolina Costa Pereira, with emphasis on her involvement in the field of mathematics education and her teaching activities (2013-2021). It is theoretically anchored in the assumptions of Cultural History to develop a hermeneutic biography through a free interview in oral history developed with the biographer herself. The results infer that Ana Carolina is a woman who had a privileged background in private basic education institutions in Fortaleza-CE, followed by a degree in Mathematics, masters, doctorate and post-doctorate in public universities in the field of mathematics education. Its pedagogical practice is based on the horizontal relationship with students and on the development of interactive and contextualized classes that encourage critical thinking. A woman's expertise in the field of mathematics, historically dominated by men, is demonstrated. Key words: Biography; Education of women; Mathematics Education; Woman in science.